Lab-based x-ray nanoCT imaging - Muller, Mark; Allner, Sebastian; Ferstl, Simone; Dierolf, Martin; Tuohimaa, Tomi; Pfeiffer, Franz (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
Due to the recent development of transmission X-ray tubes with very small focal spot sizes, laboratory-based CT imaging with sub-micron resolutions is nowadays possible. We recently developed a novel X-ray nanoCT setup featuring a prototype nanofocus X-ray source and a single-photon counting detector. The system is based on mere geometrical magnification and can reach resolutions of 200 nm. To demonstrate the potential of the nanoCT system for biomedical applications we show high resolution nanoCT data of a small piece of human tooth comprising coronal dentin. The reconstructed CT data clearly visualize the dentin tubules within the tooth piece.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CT imaging; Dentin tubules; MicroCT; NanoCT; Tooth; X-ray imaging; X-rays